Terje Larsen; Regulatory aspects of adipose tissue metabolism in reindeer - seasonal interactions - Skjenneberg (ed.), Sven (Rangifer, 1985)
The thesis Regulatory aspects of adipose tissue metabolism in reindeer - seasonal interactions by Terje Larsen is approved for the Phil, dr's degree at the University of Tromsø, Norway. The dissertation took place in Tromsø March 9, 1985.